(3EOGQI GdeTJQjGJ hGdeHjYGJ hGdeNGRf (B/s - (3GdUjQaj, eMeOs; (3HhLjQj, MSf eMeOs ((3GdHMQjf(B: s (3eDSSI dhQO GdYGdejI ddTDhf GdLGeYjI(B, s, 2006)
(3eGgjI GdTQGA hCgejJg, JfXje EOGQI GdehGQO, GdCUhd GdYdejI ddTQGA, eaghe GdeNRhf hCfhGYg, ELQGAGJ GdJNRjf, GdHjY GdTNUj(B. s
(3HjHdjhZQGajG(B: (3U(B.130s
Keywords: (3GdGOGQIs; (3GdeNRhfs